Sorbtion-Photometric Determination Of Lead (II) Ion By Organic Reagent 1,3,4-Thiadiazole2,5-Ditiol (Eurasian Research Bulletin, 2023)
" Almalyk KMK" was selected as the organic analytical reagent 1,3,4-thiadiazole2,5-ditiol for the lead (II) ion contained in the wastewater technological waters of JSC in industrial and environmental facilities. The conditions of immobilization of 1,3,4- thiadiazole-2,5-ditiol organic organic reagent to different fiber carriers have been studied.